Sarcoidosis extent relates to molecular variability. (27th March 2017) - Monast, C S; Li, K; Judson, M A; Baughman, R P; Wadman, E; Watt, R; Silkoff, P E; Barnathan, E S; Brodmerkel, C
Summary: The molecular basis of sarcoidosis phenotype heterogeneity and its relationship to effective treatment of sarcoidosis have not been elucidated. Peripheral samples from sarcoidosis subjects who participated in a Phase II study of golimumab [anti-tumour necrosis factor (TNF)-α] and ustekinumab [anti-interleukin (IL)−12p40] were used to measure the whole blood transcriptome and levels of serum proteins. Differential gene and protein expression analyses were used to explore the molecular differences between sarcoidosis phenotypes as defined by extent of organ involvement. The same data were also used in conjunction with an enrichment algorithm to identify gene expression changes associated with treatment with study drugs compared to placebo. Our analyses revealed marked heterogeneity among the three sarcoidosis phenotypes included in the study cohort, including striking differences in enrichment of the interferon pathway. Conversely, enrichments of multiple pathways, including T cell receptor signalling, were similar among phenotypes. We also identify differences between treatment with golimumab and ustekinumab that may explain the differences in trends for clinical efficacy observed in the trial. We find that molecular heterogeneity is associated with sarcoidosis in a manner that may be related to the extent of organ involvement. These findings may help to explain the difficulty in identifying clinically efficacious sarcoidosis treatments and suggest hypotheses for improved therapeutic strategies. Graphical Abstract: